2011
DOI: 10.1002/dvdy.22760
|View full text |Cite
|
Sign up to set email alerts
|

Slow stretching that mimics embryonic growth rate stimulates structural and mechanical development of tendon‐like tissue in vitro

Abstract: A distinctive feature of embryonic tendon development is the steady increase in collagen fibril diameter and associated improvement of tissue mechanical properties. A potential mechanical stimulus for these changes is slow stretching of the tendon during limb growth. Testing this hypothesis in vivo is complicated by the presence of other developmental processes including muscle development and innervation. Here we used a cell culture tendon-like construct to determine if slow stretch can explain the increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 31 publications
3
58
0
Order By: Relevance
“…Another study used a gel-nanofiber model to demonstrate that a nanoscale tip probes single collagen fibrils and proteoglycan components of cartilage, whereas a microscale tip measures a cross-linked network (28). Accordingly, nanoscale moduli were, on average, two-to threefold lower than microscale moduli in our study, and both were one to three orders of magnitude below reported chick tendon bulk tensile moduli (8,33). We also measured an increase in the SD of average Fig.…”
Section: Discussionsupporting
confidence: 51%
“…Another study used a gel-nanofiber model to demonstrate that a nanoscale tip probes single collagen fibrils and proteoglycan components of cartilage, whereas a microscale tip measures a cross-linked network (28). Accordingly, nanoscale moduli were, on average, two-to threefold lower than microscale moduli in our study, and both were one to three orders of magnitude below reported chick tendon bulk tensile moduli (8,33). We also measured an increase in the SD of average Fig.…”
Section: Discussionsupporting
confidence: 51%
“…The Role of Loading in Tendon Development and Homeostasis Tendon Development Mechanical forces during development are vital to successful limb and musculoskeletal tissue formation during embryogenesis [17][18][19][20][21][22][23][24] .…”
Section: Tendon Structure and Functionmentioning
confidence: 99%
“…For example, the menisci of the tibiofemoral joint and the plantar tarsal sesamoid of the tibiotarsal joint fail to form, suggesting the inability of tendinous structures to form properly in the absence of mechanical loading and the importance of mechanical stress for proper musculoskeletal development 18 . It is postulated that embryonic and early postnatal growth of tendon relies on the generation of two types of stresses: rapid muscular activity and slow, growth-related elongation of bone 21 . Early in tendon development, the collagen fibril diameter is characterized as a homogeneous distribution of small fibrils (ranging from approximately 40 to 75 nm).…”
Section: Tendon Structure and Functionmentioning
confidence: 99%
“…23,24 Alternatively, fibrin gels have been recently proposed for creating tissue constructs in vitro, as fibrin promotes greater collagen synthesis than collagen gels and more readily remodels according to the physical boundary conditions of the construct apparatus. [25][26][27] Cells in fibrin gels also appear to recapitulate aspects of native tendon development in vitro 28,29 and exhibit improved cell-derived collagen organization in response to mechanical stimulation. 30,31 However, research has not yet been conducted that directly compares how collagen and fibrin materials affect the ability of TLPs to respond to mechanical stimuli and produce an organized ECM.…”
Section: Introductionmentioning
confidence: 99%